Developing English Teaching Material of Reading Comprehension For Islamic Students At MTS SKB 3 Menteri Bingkat - Yunita, Ratna; Risnawaty (PT Inovasi Pratama Internasional, 2026)
According to Bryman’s model, the research procedure involves several systematic stages: (1) identifying theoretical foundations, (2) formulating hypotheses, (3) designing the research, (4) operationalizing variables, (5) collecting data, (6) quantitatively analyzing data, (7) drawing conclusions, and (8) revising or confirming theoretical implications. These steps guided the development and validation of the discovery-learning model throughout the study. Data were collected through reading comprehension tests, expert validation, and student response questionnaires. The pre-test total score was 1,200, while the post-test total score increased to 2,270, indicating a significant improvement in students’ reading comprehension achievement. Statistical analysis confirmed that Discovery Learning significantly improved students’ ability to identify main ideas, infer meanings, and comprehend textual details. Validation by material experts indicated that the developed product was valid, effective, and practical for classroom implementation. The students’ responses also reflected positive perceptions of the learning process, particularly in terms of motivation and engagement. Based on the findings, it can be concluded that the Discovery Learning-based reading comprehension model developed through the quantitative R Therefore, it is recommended that English teachers apply this model to enhance students’ analytical and interpretive reading skills. The researcher used a classroom action research (C.A.R) that was conducted in two cycles in which every cycle consisted of four meetings; this study used a qualitative approach. The location of this research was eighth-grade students of MTs SKB 3 Menteri Bingkat, with a total of 28 students